Cooperation between Management Boards and Auditors as a Factor in Good Practices - Buk, Halina (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
Polish Financial Supervision Authority and the Warsaw Stock Exchange have for several years been promoting the rules of good practice and their use by public interest entities. Practice shows that more and more large entities systematically use good practices, with some exceptions. The article examines the cooperation that occurs between corporate organs of the companies and auditors, presenting it as an important factor in corporate governance. In the recommended principles this area is treated as being of secondary importance. For the audit committee, it is only monitoring and coordinating the process of auditing financial statements that are recommended. Auditing committees are created only when there are more than five members sitting on the supervisory board. However, the majority of Polish companies have five-member boards. The conclusion, therefore, is that cooperation between corporate management boards and auditors is very restricted.